The effects of alphabetic literacy, linguistic-processing demand and tone type on the dichotic listening of lexical tones - Shao, Jing; Zhang, Caicai; Zhang, Gaoyuan; Zhang, Yubin; Pattamadilok, Chotiga (Frontiers in Psychology, 2022)
Brain lateralization of lexical tone processing remains a matter of debate. In this study we used a dichotic listening paradigm to examine the influences of the knowledge of Jyutping (a romanization writing system which provides explicit Cantonese tone markers), linguistic-processing demand and tone type on the ear preference pattern of native tone processing in Hong Kong Cantonese speakers. While participants with little knowledge of Jyutping showed a previously reported left-ear advantage (LEA), those with a good level of Jyutping expertise exhibited either a right-ear advantage or bilateral processing during lexical tone identification and contour tone discrimination respectively. As for the effect of linguistic-processing demand, while an LEA was found in acoustic/phonetic perception situations, this advantage disappeared and was replaced by a bilateral pattern in conditions that involved a greater extent of linguistic processing, suggesting an increased involvement of the left hemisphere. Regarding the effect of tone type, both groups showed an LEA in level tone discrimination, but only the Jyutping group demonstrated a bilateral pattern in contour tone discrimination. Overall, knowledge of written codes of tones, greater degree of linguistic processing and contour tone processing seem to influence the brain lateralization of lexical tone processing in native listeners of Cantonese by increasing the recruitment of the left-hemisphere language network.